Effect of green synthesised iron nanoparticles on seedling traits in Stylosanthes hamata - KUMAR, VINOD; M, JAYASHREE; DODDAMANI, SEEMA S (The Indian Journal of Agricultural Sciences, 2025)
The experiment was conducted to evaluate the effect of green-synthesised iron nanoparticles (FeNPs) using papaya (Carica papaya) leaf extract on seed dormancy and seedling traits of Stylosanthes hamata, an important forage legume. The FeNPs exhibited an absorption peak at 328.2 nm in the UV-Vis spectrum and an average particle size of 67.8 nm as determined by PSA. Seed priming with green-synthesised FeNPs significantly influenced the seed quality parameters of S. hamata. Among the treatments, FeNPs at 80 ppm (T6) recorded the highest seed germination (59.67%), root length (4.13 cm), shoot length (4.32 cm), seedling vigour index-I (504), speed of germination (15.59), and seedling dry weight (34.23 mg), along with a lower proportion of hard seeds (29.33%) and abnormal seedlings (4%), compared to the control. However, higher concentrations of FeNPs (100 ppm and 120 ppm) adversely affected germination and seedling growth. Therefore, green-synthesised iron nanoparticles can be effectively used as an alternative, eco-friendly seed treatment method to overcome hard seed coat dormancy in Stylosanthes hamata.